(untitled) (Marketing Journal, 2026)
This article examines the factors influencing the development of a commercial strategy for a retail enterprise and the methods for analyzing the environment in which the enterprise operates. A SWOT analysis is conducted, and the competitiveness of a specif ic retail enterprise is assessed.